2013
DOI: 10.1289/ehp.1205485
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Function of Adipose Tissue: Focus on Persistent Organic Pollutants

Abstract: Background: Adipose tissue (AT) is involved in several physiological functions, including metabolic regulation, energy storage, and endocrine functions.Objectives: In this review we examined the evidence that an additional function of AT is to modulate persistent organic pollutant (POP) toxicity through several mechanisms.Methods: We reviewed the literature on the interaction of AT with POPs to provide a comprehensive model for this additional function of AT.Discussion: As a storage compartment for lipophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
230
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(239 citation statements)
references
References 96 publications
6
230
1
2
Order By: Relevance
“…Dense AP contain the largest number of C, H, and O, metals, such as Na and Ca, and chemical compounds containing hydroxide and carboxide groups. This could be due to the deposition property of lipids at chronic metabolic intoxication [23].…”
Section: Resultsmentioning
confidence: 99%
“…Dense AP contain the largest number of C, H, and O, metals, such as Na and Ca, and chemical compounds containing hydroxide and carboxide groups. This could be due to the deposition property of lipids at chronic metabolic intoxication [23].…”
Section: Resultsmentioning
confidence: 99%
“…the link between obesity, immuiny and in ammation is well documented (60,61). Likewise, various CYPs were found to be expressed in the adipose tissue which appears to be a "postliver" major organ involved in the activity of xenobiotic/drug metabolizing enzymes (62)(63)(64). Impaired immune response in animals and humans a ected by obesity, leading to increased risks of infection.…”
Section: Obesity Immune System and Drug Toxicitymentioning
confidence: 99%
“…However, in the long term, this accumulation can lead to larger body burdens, which are then slowly released into the blood stream. When there is large mobilization of adipose tissue, such as during periods of weight loss, pregnancy, after pregnancy and during breastfeeding, the POPs may be released at a faster rate from adipose tissue into the blood stream [29]. Several studies have shown that after large weight losses, like after bariatric surgery, there are higher serum levels of POPs [30•, 31].…”
Section: Introductionmentioning
confidence: 99%
“…POPs may induce obesogenic effects and also induce a pro-inflammatory state that can lead to the metabolic syndrome and diabetes [29,32,33]. These effects may also be age/period of development specific [34].…”
Section: Introductionmentioning
confidence: 99%